2024
DOI: 10.3389/fendo.2024.1280983
|View full text |Cite
|
Sign up to set email alerts
|

Causal relationship between gut microbiota and polycystic ovary syndrome: a literature review and Mendelian randomization study

Junwei Sun,
Mingyu Wang,
Zhisheng Kan

Abstract: IntroductionNumerous studies have suggested an association between gut microbiota and polycystic ovarian syndrome (PCOS). However, the causal relationship between these two factors remains unclear.MethodsA review of observational studies was conducted to compare changes in gut microbiota between PCOS patients and controls. The analysis focused on four levels of classification, namely, phylum, family, genus, and species/genus subgroups. To further investigate the causal relationship, Mendelian randomization (MR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…The change in gut microbiota might be the result and the cause of the PCOS phenotype. Moreover, amelioration of gut microbiota might improve the PCOS phenotype ( Starling, 2021 ; Salehi et al, 2024 ; Sun et al, 2024 ).…”
Section: Discussionmentioning
confidence: 99%
“…The change in gut microbiota might be the result and the cause of the PCOS phenotype. Moreover, amelioration of gut microbiota might improve the PCOS phenotype ( Starling, 2021 ; Salehi et al, 2024 ; Sun et al, 2024 ).…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary data showed elevated LPS, LPS-binding protein, and zonulin levels, and a beneficial effect of probiotics and synbiotics. A subsequent review of 18 observational studies found a significant difference in 64 gut microbiota taxa between women with PCOS and controls [ 212 ]. A recent meta-analysis of microbiota studies reported that there are specific microbial communities closely associated with PCOS [ 213 ].…”
Section: Mechanisms Of Action Of Nutritional Factors In the Pathophys...mentioning
confidence: 99%
“…In addition to these observational data, four recent Mendelian randomization studies have investigated a possible causal relationship between the gut microbiome and PCOS. Three studies concluded that there was a causal relationship [ 212 , 213 , 216 ], and one study did not support a causal relationship [ 217 ]. In summary, accumulating evidence supports a role for the gut microbiome in the pathogenesis of PCOS via a variety of possible mechanisms.…”
Section: Mechanisms Of Action Of Nutritional Factors In the Pathophys...mentioning
confidence: 99%
“…A large number of studies have found that intestinal flora and its metabolites have the potential to regulate the hypothalamic-pituitary axis and luteinizing hormone secretion through the gut axis, and that the imbalance of intestinal microbiota is associated with HA, insulin resistance, chronic inflammation, and metabolic disorders related to PCOS ( Guo et al., 2023 ; Sun et al., 2024 ). Studies reveal a reduced relative abundance of Lactobacillus , Ruminococcus , and Clostridium , coupled with elevated Prevotella levels, in the intestines of PCOS-afflicted rats ( Guo et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%